CO2 responsive expansion hydrogels with programmable swelling for in-depth CO2 conformance control in porous media. (15th January 2023) - Wu, Yining; Liu, Qixin; Liu, Dayu; Cao, Xiao Peng; Yuan, Bin; Zhao, Mingwei
Highlights: CO2 responsive (CR) hydrogel was prepared, which has good injection performance and can form gel in-situ. The novel hydrogel can expand more than 10 times in acidic conditions (pH ∼ 4.5) with respect to about 2 times (pH ∼ 7). CO2 can increase the hydrophilicity and electrostatic repulsion of hydrogel, leading to programmable swelling. Abstract: Considerable research efforts have been devoted to finding and developing the oil locked within low-permeability reservoirs. The oil-rock interaction exacerbated in tiny pores and heterogeneities in formation epitomize the challenges accompanying the development of low-permeability reservoirs. CO2 flooding has become a promising treatment to increase displacement efficiency and formation energy for enhanced oil recovery. Nevertheless, due to the mismatch in the viscosity of CO2 with that of the crude oil and the intrinsic heterogeneity of the reservoir, gas channeling is inevitable, resulting in low oil recovery and low CO2 storage efficiency. This paper is motivated to fabricate CO2 intelligent responsive hydrogel that exhibits a delayed swelling: the hydrogel will uptake water and swell when encountering CO2 or H +, to strengthen the plugging capacity for the gas channeling. A two-step method was used to prepare CO2 responsive (CR) hydrogel which has good injection performance and can form gel in-situ to control the gas channeling in low-permeability reservoirs. To achieve the above functions, CR polymer with acrylamide (AM) and N-[3-(Dimethylamino) propyl] methacrylamide (DMAPMA) was synthesized by aqueous free-radical copolymerization. CR hydrogel was prepared by crosslinking CR polymer with polyethyleneimine (PEI). Then 1.2 wt% CR polymer and 0.2 ∼ 0.4 wt% PEI were determined as the optimal synthetic formulation of CR hydrogel which is capable of maintaining stability at 80 ℃ for more than 30 days without dehydration. The gelation time was more than 24 h indicating that the CR hydrogel has good injection and in-depth migration ability. Also, the swelling behaviors of CR hydrogel were studied, and the hydrogel can expand more than 10 times in acidic conditions (pH ∼ 4.5) with respect to about 2 times in neutral conditions (pH ∼ 7). The expansion mechanism is further revealed and proved to be feasible for CO2 channeling control.